STRATEGI PEMBELAJARAN GURU AGAMA HINDU RELEVANSINYA DALAM PENGEMBANGAN KECERDASAN EMOSIONAL SISWA KELAS X IPA 1 SMA NEGERI 1 SUKASADA - Komang Trisna Mahartini (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
This study aims to 1) describe the strategy of Teacher of Hindu Religion SMA Negeri 1Sukasada. 2) to describe the emotional intelligence of the students of class X IPA 1 in SMANegeri 1 Sukasada. 3) to describe the relevance of teacher's learning strategy in developingemotional intelligence of X IPA 1 students in SMA Negeri 1 Sukasada. The method of this researchis qualitative (analytical descriptive). Research data in the form of facts related to teacher learningstrategies and students' emotional intelligence. The main instrument in this study is the researchersthemselves. In addition to the main instruments, researchers are also assisted with a companioninstrument that is observation guides, interview guides, and questionnaires. The number ofteachers who become the source of data is 1 person and the number of students who become thedata source is 9 people. The data source was chosen using purposive sampling technique. Datawere taken through observation, interview, documentation, and questionnaire. Analysis is doneduring and after data collection, data analysis phase is data reduction, data exposure, and dataverification. The research took place at SMA Negeri 1 Sukasada. The result of research that is 1)Teachers have been able to apply contextual learning strategy. 2) The emotional intelligence ofstudents tends to be well characterized by the emergence of dimensions recognizing emotions ofself, managing emotions, motivating, recognizing the emotions of others, and fosteringrelationships with others. 3) Teaching strategies applied by the teacher seen from the planningand implementation have been able to develop the five dimensions of students' emotionalintelligence.